MACROECONOMIC FACTORS ON NON-PERFORMING FINANCING IN INDONESIAN ISLAMIC BANK: ERROR CORRECTION MODEL APPROACH - Ikramina, Cyntia; Sukmaningrum, Puji Sucia (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2021)
Non-performing Financing (NPF) is a ratio to measure the non-performing finance level in Islamic banks and one indicator of Islamic banking's health. The higher NPF indicates the quality of the bank's financing was terrible. This study aims to determine several macroeconomic factors on the NPF ratio in Islamic commercial banks in Indonesia. This study applies Error Correction Model (ECM) with saturated sample methods. Sources of data from the official websites of the Financial Authority Services (OJK), Bank Indonesia (BI), and Indonesia Statistics Bureau (BPS). The sample used was Islamic commercial banks in all periods starting from January 2014 to February 2020 published in Islamic banking statistics. There are 74 Islamic commercial banks as observations. The results of this study are pretty surprising. In the short term, macroeconomic variables influence the NPF ratio in Islamic banks, while only inflation affects the NPF for a long time. The government needs to be more able to control when giving policies to increase inflation due to the impact of problematic Financing in Islamic banking. If it occurs continuously, the bank will threaten with bankruptcy. For the Islamic banking industry, we hoped that it could be wiser in placing the liquidity owned, especially when it comes to giving the financing, must carefully look at the customer's portfolio. This study provides comprehensive information on the macroeconomic impact on non-performing financing, specifically on Islamic banks in Indonesia.